ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN USAHATANI UBI BANGGAI DI KECAMATAN TOTIKUM SELATAN KABUPATEN BANGGAI KEPULAUAN - Moh. Sunandar Maika; Saiful Darman; made antara (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
Banggai Kepulauan district has potency and investment opportunities in agricultural sector particularly food crop sub sector whichis based on local priority commodities.  One of the food crops that have investment opportunity is Banggai yum.  It is the original food source for people in Banggai Kepulauan district which has been practiced from generation to generation.  The development of Banggai yum currently is still in the stage of yet becoming value added products.  In general, the people consume Banggai yum by simply processing it either through boiling or frying, thus it has not yet processed into flour or noodle or other type of processed products. The aims of this research were (1) to determine the income of Banggai yum farming system in South Totikum sub district of Banggai Kepulauan district and (2) to determine the development strategy of Banggai yum farming system in South Totikum       sub district of Banggai Kepulauan district.  The research location was purposively determined   based on the largest land area size of Banggai yum cultivation.  Income analysis was used to analyze the farming system income with the equation of π = TR – TC to generate R/C  value, while the development strategy was analyzed using SWOT analysis.  The research   results showed that Banggai yum is feasible to be developed with the W – O (Weaknesses-Opportunities) strategy.  The programs and activities to support the strategy include (1) utilizing climate and land suitability in which no shifting cultivation is adopted, (2) promoting Banggai yum through tourism sector by introducing local wisdom, thus easily opening market accessibility, and (3) utilizing Banggai yum potency and high economy value to attract investment for increasing value added of its end products. Keywords: Banggai yum, Farming System, Income, and SWOT.